The Literacy In Food Blog: The Modes Of Perssuasion In Anakjajan.com - Josua Lumban Gaol; Gresia Wydia; Rita Hartati (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
In the digital era, food blogs have emerged as influential platforms for sharing culinary experiences and shaping consumer preferences. This study focuses on Anakjajan.com, a prominent Indonesian food blog, to analyze the persuasive strategies employed in its content and their impact on readers' food literacy. Utilizing Aristotle's modes of persuasion—ethos (credibility), pathos (emotion), and logos (logic)—the research examines how these elements contribute to the blog's effectiveness in influencing food choices. Ethos is established through the author's expertise and authentic reviews, while pathos engages readers with evocative language and appealing visuals. Logos provides factual information about food quality and dining options. A qualitative approach was employed, involving content analysis of blog posts and surveys to assess the influence of these persuasive strategies on readers' decision-making processes. The findings reveal that understanding these modes of persuasion is essential for enhancing digital literacy, as they enable readers to critically evaluate online content and make informed culinary choices.